CHARACTER EDUCATION IN CONTENT COURSES: SELF-SCORING AS A MEANS FOR DEVELOPING HONESTY IN STUDENTS - Djiwandono, Patrisius Istiarto (TEFLIN Journal, 2016)
As character education is gaining currency, some institutions have started to incorporate character education into its instructional practices. However, this is not an easy task. Limited hours of contact and teachers’ insufficient know-how of teaching and evaluating students’ characters have hampered the efforts. This paper reports a small effort to shape students’ honesty through self-scoring techniques. An intact class of 19 students who were taking a content course were instructed to self-score their own works in two different tests. Their scores were then compared to the lecturer’s scoring. It was found that the students tend to be honest when the test was not weighted substantively, but increasingly over-rated themselves on a high-stake test. The paper then discusses the potential and possible weaknesses of self-scoring technique as a means of cultivating honesty.